2012
DOI: 10.1016/j.stem.2012.02.021
|View full text |Cite
|
Sign up to set email alerts
|

Direct Reprogramming of Fibroblasts into Neural Stem Cells by Defined Factors

Abstract: Recent studies have shown that defined sets of transcription factors can directly reprogram differentiated somatic cells to a different differentiated cell type without passing through a pluripotent state, but the restricted proliferative and lineage potential of the resulting cells limits the scope of their potential applications. Here we show that a combination of transcription factors (Brn4/Pou3f4, Sox2, Klf4, c-Myc, plus E47/Tcf3) induces mouse fibroblasts to directly acquire a neural stem cell identity-wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

12
430
2
5

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 500 publications
(453 citation statements)
references
References 39 publications
12
430
2
5
Order By: Relevance
“…Transdifferentiation from other type of somatic cells into functional neurons has allowed the generation of mature neurons in a relatively shorter period, which seems to be an ideal source of cells for transplantation, nevertheless, the efficiency of transdifferentiation is low, and the iNs are not expandable for large quantity. Alternative procedures that convert other type of somatic cells into expandable neural stem cells are also under extensive exploration (Kim et al, 2011;Han et al, 2012;Lujan et al, 2012;Ring et al, 2012;Sheng et al, 2012;Thier et al, 2012). In contrast to the iNs, the induced neural stem cells (iNSCs) are capable to proliferate, thus allow yield of larger quantity of cells through selectively amplification of the induced neural stem cells.…”
Section: Introductionmentioning
confidence: 99%
“…Transdifferentiation from other type of somatic cells into functional neurons has allowed the generation of mature neurons in a relatively shorter period, which seems to be an ideal source of cells for transplantation, nevertheless, the efficiency of transdifferentiation is low, and the iNs are not expandable for large quantity. Alternative procedures that convert other type of somatic cells into expandable neural stem cells are also under extensive exploration (Kim et al, 2011;Han et al, 2012;Lujan et al, 2012;Ring et al, 2012;Sheng et al, 2012;Thier et al, 2012). In contrast to the iNs, the induced neural stem cells (iNSCs) are capable to proliferate, thus allow yield of larger quantity of cells through selectively amplification of the induced neural stem cells.…”
Section: Introductionmentioning
confidence: 99%
“…More recently, several independent groups have shown that a combination of transcription factors could directly reprogram mouse fibroblasts toward stably expandable induced neural stem cells (Han et al, 2012;Thier et al, 2012). These studies present alternative strategies for reprogramming somatic cells to neural stem cell identity.…”
Section: Direct Reprogramming Of Non-neural Cells To Neural Stem Cellsmentioning
confidence: 99%
“…Han et al showed that reprogramming with a combination of transcription factors (Brn4/Pou3f4, Sox2, Klf4, c-Myc, plus E47/Tcf3) directly induced neural stem cell identity in mouse fibroblasts and that iNS cells did not generate teratomas after injection into immunosuppressed mice (Han et al, 2012). The multipotent iNS cells display NS cell morphology, differentiation capacity, and self-renewing potential with gene expression features and epigenetic profiles similar to those of brain-derived NS cells.…”
Section: Direct Reprogramming Of Non-neural Cells To Neural Stem Cellsmentioning
confidence: 99%
See 1 more Smart Citation
“…iPS cells exhibit properties very similar to ES cells and can give rise to an entire organism. Similarly, fibroblasts are readily reprogrammed into neural cells and neural stem cells by expression of yet another sets of transcription factors [3][4][5]. Furthermore, procedures were developed that allow the development of three-dimensional organ-like structures in vitro from tissue-resident adult stem cells or pluripotent stem cells, referred to as organoids [6,7].…”
mentioning
confidence: 99%